Liquid and spray-dried nanoemulsion designs for pulmonary delivery of rifampicin / Kifayat Ullah Shah - Shah, Kifayat Ullah (Institute of Graduate Studies, UiTM, 2017)
The study investigated the aerosolization and inhalation profiles of rifampicin-oleic acid first generation liquid and solid nanoemulsions and their respective chitosan- and chitosan-folate conjugate-decorated second and third generation nanoemulsions. The liquid nanoemulsions were prepared by spontaneous emulsification method and had their size, zeta potential, polydispersity index, morphology, pH, viscosity, surface tension, density, refractive index, drug content, drug release, aerosolization and inhalation profiles characterized. The first, second and third generation nanoemulsions had average droplet sizes of 43.89 ± 0.36 nm, 52.12 ± 0.36 nm and 59.69 ± 0.26 nm, with narrow polydispersity indices at 0.16 ± 0.03, 0.25 ± 0.03 and 0.23 ± 0.01 respectively. They exhibited desirable pH, surface tension, viscosity, refractive index, density, and viscosity attributes for pulmonary rifampicin administration. The second generation nanoemulsion was characterized by relatively low levels of burst drug release due to intimate chitosan packing at the oil globules’ surfaces and viscosifying effect on continuous phase, which was unattainable by the branched folate conjugate of chitosan. All nanoemulsions demonstrated more than 95 % aerosol output and inhalation efficiency greater than 75 % when delivered by nebulization. The aerosol output, aerosolized and inhaled fine particle fractions were primarily governed by the size and surface tension of nanoemulsions in an inverse relationship. The first, second and third generation nanoemulsions were converted to their corresponding solid counterparts by spray drying method…